Edukasi dan Implementasi Teknik Relaksasi Benson dalam Mengurangi Nyeri pada Pasien Dewasa Post Operasi - Muhammad Azra Razi; Septian Mixrova Sebayang; Arlyana Hikmanti (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Background: The number of surgical procedures has increased significantly from year to year. One of the complications that often occurs after surgery is postoperative pain. Postoperative pain will begin to be felt after the effects of anesthesia wear off. The management of this pain is divided into two categories: pharmacological drug management and non-pharmacological relaxation management. The use of analgesics as primary therapy has limitations and risks of side effects, so it needs to be combined with non-pharmacological relaxation methods, such as the Benson relaxation technique. The Benson relaxation technique is a simple method that combines breathing techniques with spiritual aspects, aiming to reduce the activity of the sympathetic nervous system that triggers pain and anxiety. To address these issues, a community service activity on Benson relaxation education was conducted to prevent patients from becoming dependent on antibiotics. Objective. This Community Service (PkM) aims to increase knowledge about Benson relaxation and reduce the pain scale of post-operative patients using Benson relaxation techniques. Methods. This Community Service includes audio-visual media-based education and the implementation of Benson relaxation on 30 adult post-operative patients in the Ar-rahman RSI Purwokerto inpatient ward. Evaluation was conducted through pain scale measurements using the Numeric Rating Scale (NRS), as well as assessments of patients' knowledge before and after education using pre-test and post-test questionnaires. Results. This activity demonstrated a significant improvement in patients' understanding of Benson relaxation techniques, with 86.7% of participants initially having insufficient knowledge, but after education, 93.3% improved to the “good knowledge” category. Additionally, the pain scale decreased by an average of 1.9 points, with the majority of patients experiencing severe pain (43.3%) before the intervention, which improved to moderate pain (60%) after implementation. Thus, education and training in Benson relaxation techniques were proven effective as a non-pharmacological intervention in reducing post-operative pain.